Social accounting matrices for Mozambique, 1994 and 1995 - Arndt, Channing; Cruz, Antonio; Jensen, Henning Tarp; Robinson, Sherman; Tarp, Finn (International Food Policy Research Institute, 1998)
This working paper documents the construction of the 1994 and 1995 Mozambican social accounting matrices (SAMs). The aggregate macro-SAM is called MACSAM, and the disaggregated version is MOZAM. With 13 agricultural and two agricultural processing activities, the primary sectors are particularly well represented in MOZAM. There are also 40 commodities, and the three factors of production: agricultural and non-agricultural labour, and capital. Two household types (urban and rural) are identified, and government expenditure is divided into two separate accounts, recurrent government and government investment. MOZAM includes a number of innovative features, partly reflected in household demand, where a distinction is made between home consumption of own production and private consumption of marketedcommodities. Home consumption avoids trade and transport margins. Thus, MOZAM captures prevailing incentives for households to avoid markets and function more as autonomous production/consumption units. The disaggregation of household demand brings marketing margins in focus in relation to decisions regarding production. However, transactions costs are also important for exported and imported commodities. Domestic, export and import marketing margins are therefore explicitly broken out for each activity in MOZAM. Procedures used to balance MACSAM and MOZAM are also documented, including the use of maximum entropy methods to estimate the SAMs, which make efficient use of all available data in a framework that incorporates prior information and constraints.